Characteristics and potential biomarkers of flavor compounds in four Chinese indigenous chicken breeds - Xiong, Xinwei; Ma, Jinge; He, Qin; Chen, Xiaolian; Wang, Zhangfeng; Li, Longyun; Xu, Jiguo; Xie, Jinfang; Rao, Yousheng (Frontiers in Nutrition, 2023)
Chinese indigenous chickens have a long history of natural and artificial selection and are popular for their excellent meat quality and unique flavor. This study investigated six meat quality-related traits in Ningdu yellow, Baier yellow, Kangle, and Shengze 901 chickens. Two-dimensional gas chromatography-time-of-flight mass spectrometry was used to detect unique flavors in 24 breast muscle samples from the same phenotyped chickens. Overall, 685, 618, 502, and 487 volatile organic compounds were identified in Ningdu yellow, Baier yellow, Kangle, and Shengze 901 chickens, respectively. The flavor components were separated into eight categories, including hydrocarbons and aldehydes. Multivariate analyses of the identified flavor components revealed some outstanding features of these breeds. For example, the hydrocarbons (22.09%) and aldehydes (14.76%) were higher in Ningdu yellow chickens and the highest content of N, N-dimethyl-methylamine was in Ningdu yellow, Baier yellow, and Shengze 901 chickens, indicating the maximum attribution to the overall flavor (ROAV = 439.57, 289.21, and 422.80). Furthermore, we found that 27 flavor compounds differed significantly among the four Chinese breeds, including 20 (e.g., 1-octen-3-ol), two (e.g., 2-methyl-naphthalene), four (e.g., 2,6-lutidine), and one (benzophenone) flavor components were showed significant enrichment in Ningdu yellow, Baier yellow, Kangle, and Shengze 901 chickens, respectively. The flavor components enriched in each breed were key biomarkers distinguishing breeds and most were significantly correlated with meat quality trait phenotypes. These results provide novel insights into indigenous Chinese chicken meat flavors.